2018
DOI: 10.1021/acs.jpclett.7b03439
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental–Theoretical Study of the OH + CO → H + CO2 Reaction Dynamics

Abstract: A combined experimental-theoretical study is performed to advance our understanding of the dynamics of the prototypical tetra-atom, complex-forming reaction OH + CO → H + CO, which is also of great practical relevance in combustion, Earth's atmosphere, and, potentially, Mars's atmosphere and interstellar chemistry. New crossed molecular beam experiments with mass spectrometric detection are analyzed together with the results from previous experiments and compared with quasi-classical trajectory (QCT) calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…As shown in Figure , the reaction profile of R 1 resembles that of the reaction OH + CO → H + CO 2 , a very important elementary reaction in the combustion of hydrocarbons. The HOSO and HSO 2 intermediates, similar to HOCO and HCO 2 , can isomerize to each other via the transition state TS1, and both species can produce the products H and SO 2 via different transition states, TS2 and TS3, respectively.…”
Section: Introductionmentioning
confidence: 87%
“…As shown in Figure , the reaction profile of R 1 resembles that of the reaction OH + CO → H + CO 2 , a very important elementary reaction in the combustion of hydrocarbons. The HOSO and HSO 2 intermediates, similar to HOCO and HCO 2 , can isomerize to each other via the transition state TS1, and both species can produce the products H and SO 2 via different transition states, TS2 and TS3, respectively.…”
Section: Introductionmentioning
confidence: 87%
“…barkeri-CdS BPEC system for CO 2 reduction with a CH 4 production rate of 0.19 μmol/h and a quantum efficiency of 0.34%. , However, there are some limitations for such a BPEC system, for example, the quick depletion of hole scavengers led to the photo-oxidative dissolution of CdS semiconductor quantum dots (QDs) and then the oxidative photodamage of cells . CO might help address some of those limitations through being adsorbed on the surface of CdS QDs and serving as a potential sacrificial reagent . The exact effect of CO on the metabolic activity of methanogens remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…17 CO might help address some of those limitations through being adsorbed on the surface of CdS QDs and serving as a potential sacrificial reagent. 18 The exact effect of CO on the metabolic activity of methanogens remains to be explored. Some studies showed that CO could be used as a substrate by methanogens, 19 whereas the toxic nature of CO or cellular redox imbalances building up in the CO-utilizing pathways was reported to deteriorate the methanogenesis performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this scenario, accurate state-of-the-art computational approaches play a fundamental role because they provide a powerful tool for deriving feasible reaction mechanisms as well as accurate predictions of spectroscopic parameters. Concerning reactivity, experimental investigations face difficulties in mimicking the extreme conditions that characterize the ISM (but also planetary atmospheres) in the laboratory, and they often require guidance of theory to be interpreted (see, e.g., Tizniti et al (2014);Cheikh Sid Ely et al (2013); Abeysekera et al (2015Abeysekera et al ( , 2018; Caracciolo et al (2018); Yang et al (2019); Thomas et al (2019)). However, it must be pointed out that accurate determination of reaction mechanisms by theory is at the state of the art in computational chemistry because, at the typical low temperatures of the ISM, rates are extremely sensitive to energetics and barrier heights.…”
Section: Introductionmentioning
confidence: 99%